Compliance to Universal Design Criteria in Nursing Homes of Tehran - Morteza Nasiri; Mahshid Foroughan; Vahid Rashedi; Asghar Makarem; Bahram Jafari Mourjan (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: There has been a rapid growth in the number of older people residing in the nursing homes. Therefore, it is highly important to prepare the physical milieus that are responsive to their physical, psychosocial, and spiritual needs. The universal design implies designing the products and environments in a manner that it is usable by all people, to the greatest extent possible, without the need for further adaptation. The aim of this study was to evaluate the conformity of the physical milieus of the nursing homes in Tehran to the universal design criteria. Methods & Materials: This was a cross-sectional descriptive study. All the nursing homes for older people located in the city of Tehran during the year 2015 were evaluated using the Nursing Home Physical Fitness Checklist, which consisted of 12 subscales and 70 items. Psychometric properties of this tool were evaluated and confirmed prior to the experiment. The collected data was analyzed using the measures of central tendency. Results: Majority of nursing homes in terms of kitchen, management section, laundry room, heating and cooling conditions, main entrance, treatment room, and the toilets were in conformance with the universal design criteria, while only one-third of the homes had extinguishers. The criteria was not adequately met in terms of the items of available chapel and library, staff restroom, living room, and dining hall.  Conclusion: The findings of this study showed that the majority of nursing homes evaluated did not follow the universal design criteria. Therefore, providing the proper guidelines and policies to promote the universal design observance in nursing homes is considered as a major necessity.